Letter from the Editor - Makinde, Peter Oyewole (WritingThreeSixty, 2025)
I present to you the first issue of Volume 8 of WritingThreeSixty on the theme: Africa in Perspective: Contemporary Issues in Arts and Humanities. This marks a significant milestone in our collective efforts to continue this graduate journal and invite authors from far and wide to captivate us with their academic and creative voices.